PENGEMBANGAN POTENSI DESA WISATA DAN GERAKAN SADAR WISATA DI KAWASAN JATIGEDE - Ariadne Shinta Dewi, Evie; Prasanti, Ditha; Aisha, Sarah; Ratna Suminar, Jenny; Adi Wibowo, Kunto (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2023)
The tourism awareness movement is an important aspect that must be developed in realising the development of tourism villages in Jatigede sub-district. This can be realised with the support of the local community. Therefore, the PPM programme carried out by the Communication Science Study Programme is to encourage the potential for increasing the village tourism awareness movement in Jatigede sub-district. In addition, according to the concept of tourism management, tourism in the village can also be institutionalised through the existence of Tourism Awareness Groups which will be an important force in managing tourism potential by collaborating with other parties in the village. This Community Service Programme (PPM) has been carried out in the October-November 2023 period with various series of activities. The purpose of this PPM is to create a Tourism Awareness Group (Pokdarwis) in the Jatigede area in the future. Prodi Ilkom conducted a series of surveys of village potential up to the monitoring and evaluation stage as the final PPM activity. PPM activities run smoothly supported by collaboration with the sub-district and others in the village chosen as the object of PPM Prodi Ilkom. The five villages are Kadujaya village, Cijeungjing village, Jemah village, Karedok village, and Cipicung village. The success indicators of the PPM activities were shown by the enthusiasm of the participants in following the PPM series and the initiation of Tourism Awareness Groups in some of these villages.